Proses Pemeriksaan Anggota Polri yang Diduga Melakukan Tindak Pidana di Wiliyah Hukum Polres Timor Tengah Selatan Menurut Kode Etik Kepolisian - Simon Yonas Sanak; Simplexius Simplexius; A Resopijani (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This study analyzed the process of examining members of the National Police who allegedly violated the code of conduct in the jurisdiction of the Timor Tengah Selatan (TTS) resort police. The research method used is qualitative research with a case study approach. The data was collected through in-depth interviews with the Professional and Security Division of the National Police of the Republic of Indonesia or commonly abbreviated as Div Propam Polri. The analysis was conducted to identify patterns and processes that emerged in the process of examining police members who violated the code of ethics at the TTS police station. The formulation of the problem in this study is 1. What is the process of examining and imposing sanctions on members of the National Police who are suspected of violating the code of conduct in the South Central Timor Police area? 2. How is the relationship between ethical sanctions and criminal sanctions in judicial proceedings in the District Court? The results showed that the examination process for members of the National Police who were suspected of violating the code of ethics in the jurisdiction of the South Central Timor Police was carried out in accordance with the Chief of Police Regulation Number 7 of 2022 concerning the Police Professional Code of Ethics, which involved various stages, ranging from reports or direct findings by officers, examinations to prosecutions and criminal acts in the process in accordance with the Criminal Procedure Code. In the event that a member of the National Police who violates the order of the member is immediately given disciplinary action by the ankum. This finding provides insight into efforts to improve the law enforcement system in terms of transparency in the examination process of members of the National Police who are suspected of violating the code of ethics in the jurisdiction of the TTS police.